2010
DOI: 10.1007/s00432-010-0854-3
|View full text |Cite
|
Sign up to set email alerts
|

Preventing chemoresistance of human breast cancer cell line, MCF-7 with celecoxib

Abstract: Celecoxib effectively prevents the development of chemoresistance in breast cancer cell line MCF-7 induced by doxorubicin, which was partly involved in inhibiting the expression and DNA-binding activity of nuclear transcription factors AP-1 and NF-κB and downstream expression and function of P-gp. Furthermore, cytostatic efficacy of celecoxib and doxorubicin on MCF-7 cell was synergistic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Relevant studies have demonstrated that COX-2 inhibitors increase the sensitivity of cancer cells to chemotherapeutics by regulating the activity of P-gp [12], [13]. It has been found that celecoxib, a selective COX-2 inhibitor, may downregulate P-gp expression in cancer cells by suppressing the expression of transcription factors such as NF-κB [14], [15]. Several studies indicated that the MDR-1 gene may contain DNA binding sites for transcription factor NF-κB [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies have demonstrated that COX-2 inhibitors increase the sensitivity of cancer cells to chemotherapeutics by regulating the activity of P-gp [12], [13]. It has been found that celecoxib, a selective COX-2 inhibitor, may downregulate P-gp expression in cancer cells by suppressing the expression of transcription factors such as NF-κB [14], [15]. Several studies indicated that the MDR-1 gene may contain DNA binding sites for transcription factor NF-κB [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the MCF7 breast cancer cell line, the interaction of celecoxib with these four chemotherapeutics was antagonistic, indicating that celecoxib is of little value when used in combination with antitumour drugs in the treatment of breast cancer. By contrast, other data indicate that celecoxib enhances the cytotoxicity of anticancer drugs in breast cancer cells (99,108). The interaction of celecoxib with etoposide, cisplatin and 5-FU was shown to be dependent on the cancer cell line employed, the drug type used and the incubation schedule.…”
Section: Combination Of Nsaids With Chemotherapeutic Drugs In Vitromentioning
confidence: 80%
“…Cyclooxygenase-2 (COX-2) and sphingosine kinase 2 (SphK2). It is thought that COX-2 inhibitors prevent the development of resistance to different cytostatics and that COX-2 overexpression induces increased multidrug resistance protein 1 (MRP1) expression in different cancer cells [99][100][101][102] . Schnitzer et al showed that COX-2 is upregulated under hypoxia in a HIF-1-independent fashion and sphingosine-1-phosphate (S1P) is responsible for COX-2 induction under hypoxia in A549 lung cancer cells 103 .…”
mentioning
confidence: 99%